Macronutrient intake in soccer players - A meta-analysis - Steffl, M.; Kinkorova, I.; Kokstejn, J.; Petr, M. (Nutrients, 2019)
The nutrition of soccer players is an important topic and its knowledge may help to increase the quality of this popular game and prevent possible health problems and injuries in players. This meta-analysis aims to estimate the current dietary trends of three basic macronutrients in junior and senior soccer players during the first two decades of the 21st century. We analyzed data from 647 junior players (mean age 10.0-19.3) from 27 groups, and 277 senior (mean age 20.7-27.1) players from 8 groups from altogether 21 papers in this meta-analysis. Weighted averages were calculated for each macronutrients. Protein intake is higher than recommended in both juniors, 1.9 95% confidence interval (CI) 1.8-2.0 g/kg/day, and seniors 1.8 95% CI 1.6-2.0 g/kg/day. However, carbohydrate intake is still below the recommended values in both groups (5.7 95% CI 5.5-5.9 g/kg/day in junior and 4.7 95% CI 4.3-5.0 g/kg/day in senior players). The proportion of fat as total energy intake is in concordance with the recommendations (31.5 95% CI 32.0-35.9% in junior and 33.1 95% CI 29.9-36.2% in senior players). In particular, due to possible health complications, the small carbohydrate intake should be alarming for coaches, nutritional experts, and parents.